World Health Organization grade II–III astrocytomas consist of genetically distinct tumor lineages. Issue 8 (22nd June 2016) - Hattori, Natsuki; Hirose, Yuichi; Sasaki, Hikaru; Nakae, Shunsuke; Hayashi, Saeko; Ohba, Shigeo; Adachi, Kazuhide; Hayashi, Takuro; Nishiyama, Yuya; Hasegawa, Mitsuhiro; Abe, Masato
Abstract : Recent investigations revealed genetic analysis provides important information in management of gliomas, and we previously reported grade II–III gliomas could be classified into clinically relevant subgroups based on the DNA copy number aberrations (CNAs). To develop more precise genetic subgrouping, we investigated the correlation between CNAs and mutational status of the gene encoding isocitrate dehydrogenase ( IDH ) of those tumors. We analyzed the IDH status and CNAs of 174 adult supratentorial gliomas of astrocytic or oligodendroglial origin by PCR‐based direct sequencing and comparative genomic hybridization, respectively. We analyzed the relationship between genetic subclassification and clinical features. We found the most frequent aberrations in IDH mutant tumors were the combined whole arm‐loss of 1p and 19q (1p/19q codeletion) followed by gain on chromosome arm 7q (+7q). The gain of whole chromosome 7 (+7) and loss of 10q (−10q) were detected in IDH wild‐type tumors. Kaplan–Meier estimates for progression‐free survival showed that the tumors with mutant IDH, −1p/19q, or +7q (in the absence of +7p) survived longer than tumors with wild‐type IDH, +7, or −10q. As tumors with +7 ( IDH wild‐type) showed a more aggressive clinical nature, they are probably not a subtype that developed from the slowly progressive tumors with +7q ( IDH mutant). Thus, tumors with a gain on chromosome 7 (mostly astrocytic) comprise multiple lineages, and such differences in their biological nature should be taken into consideration during their clinical management. Abstract : Genetic subgrouping based on DNA copy number aberrations and IDH1 gene mutations revealed grade II–III astrocytomas consist of multiple lineages. The differences in their biological nature should be taken into consideration during their clinical management.